(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2014)
The “neurosciences of ethics” are in many ways enriching with experimental dates the field of moral psychology, that is of the research that aims at understanding which emotions and which feelings, which capacities of ideations, imagination and reflection collaborate in sustaining and motivating a moral life. From this point of view, it becomes clear why the recent research on the brain are agitating the debate on ethics. The recent expansion of the interest of neurosciences to “not observable” aspects of the behavior, such as personality traits, emotions and moral reasoning, has led to the idea of experimental ethics (on the line of the experimental philosophy), with the right intent to correct the artificiality and of the universalism of much contemporary moral philosophy, by throwing a bridge between empirical and experimental research and normative questions. Many experiments provide however ambiguous and contradictory evidences in relation to the assumption of an original field of sharing, of an original relationality.